Ethnomedicine exploration of medicinal plants: Fumaria capreolata L. and Calendula suffruticosa Vahl in Numidia (north-eastern Algeria) - Sofiane, Ismahene; Seridi, Ratiba (Biodiversity: Research and Conservation, 2023)
Our ethnobotanical study of medicinal plants native to Numidia aimed to investigate traditional therapeutic and cosmetic uses reported by the local population, traditional practitioners, and herbalists of this region. An ethnobotanical survey was carried out using questionnaires on Calendula suffruticosa Vahl (shrub-like marigold) and Fumaria capreolata L. (climbing fumitory) in 2017-2018 in 5 cities of north-eastern Algeria. We studied the profile of 100 respondents, their knowledge of local plant names, therapeutic uses, the parts used, and the mode of use of each plant. The data collected show 62.0% of local people use these plants for several reasons, while 38% use it only for therapeutic purposes. The aerial part is the most usable for both species, especially the flower for marigold (82.0% of those who use it). According to the surveys conducted, it appears that the local communities in these cities make use of various medical properties of marigold: anti-inflammatory (37.0%), antibacterial (16.2%), against oedema (8.6%), anti-ulcer (6.1%), sedative, cholesterol-lowering (3.4%), antihypertensive, i.e. lowering blood pressure (2.6%). In contrast, the use of fumitory is rare, due to its toxicity in larger doses. In most cases, the method of administration of the remedies varies, e.g. as an infusion (72.1% of those who use fumitory), decoction (10.0%), compresses (10.8%), cream or ointment based on decoction (7.0%). This study shows the great importance of medicinal plants in the local traditional medicine of north-eastern Algeria.